Pengaruh Risiko Audit Dan Stres Kerja Terhadap Motivasi Auditor Pada Kantor Akuntan Publik Kota Padang - Marisa Eneng; Dewi Zulvia (FEB Universitas Maritim Semarang, 2023)
This research aims to find out how much influence audit risk and work stress have on the motivation of auditors at the Padang City Public Accounting Firm. In this research, the population is all auditors in public accounting offices in Padang City. The population in this study was 92 people consisting of several employees who had different positions/groups in KAP Padang City. The sampling method used was the accidental sampling method. The regression analysis carried out was multiple linear regression analysis. The research results obtained based on the partial test (t test) showed: (a) The audit risk variable has a positive and significant effect on auditor motivation. (b) The work stress variable has a positive and significant effect on auditor motivation. Meanwhile, the simultaneous test of audit risk and work stress has a positive and significant influence on auditor motivation. Auditors may be motivated by the challenge of performing high-quality audits in the face of increased audit risk. These challenges can provide a sense of accomplishment and satisfaction for auditors who successfully navigate risks and complete high-quality audits. The stress faced in challenging work situations can motivate individuals to try harder and challenge themselves. When someone feels that they can overcome or cope with a difficult task, this can increase their motivation to succeed.